Phloem‐feeding whiteflies can fool their host plants, but not their parasitoids. (5th July 2013) - Zhang, Peng‐Jun; Xu, Cai‐Xia; Zhang, Jin‐Ming; Lu, Yao‐Bin; Wei, Jia‐Ning; Liu, Yin‐Quan; David, Anja; Boland, Wilhelm; Turlings, Ted C. J.; Watling, Jennifer
Summary Herbivore attack induces plants to mobilize chemical defences, including the release of volatiles that attract natural enemies of the herbivore. This commonly involves the jasmonic acid (JA) pathway. However, phloem‐feeding whiteflies specifically trigger salicylic acid (SA)‐signalling, thereby suppressing JA‐based defences and enhancing host plant suitability. Here, we show with Arabidopsis thaliana plants that the whitefly parasitoid Encarsia formosa outsmarts this apparent host plant manipulation by exploiting the SA‐triggered emission of β‐myrcene. Assays with various Arabidopsis mutants and phytohormone and gene‐expression analyses reveal that the whiteflies induce the accumulation of endogenous SA, thereby enhancing the expression of SA‐regulated genes, one of which encodes ocimene/myrcene synthase, which resulted in the recruitment of parasitoids under greenhouse conditions. Performance assays confirmed that whiteflies directly benefit from suppressing JA‐based defences. Taken together, we conclude that by activating SA‐signalling whitefly feeding suppresses direct, JA‐based defences, but that parasitoids can adapt to this by exploiting specific, SA‐induced volatile emissions for host location. Our work further confirms that herbivory contributes to selective pressure governing the evolution of inducible volatile signals as indirect plant defences.